Synchronous malignant phyllodes tumour and invasive lobular carcinoma—case report and review. Issue 10 (8th October 2018) - To, Henry; Ong, Bee Shan; Dodd, Tom; Prasannan, Subhita
Abstract: Synchronous phyllodes tumour and invasive lobular carcinoma is an extremely rare event. We report these concurrent diagnoses in a patient observed in an ipsilateral breast, suspected due to breast risk factors (family history and lobular carcinoma in situ ) and the presence of malignant phyllodes. Screening breast magnetic resonance imaging was able to identify the carcinoma which was occult in other imaging. An understanding of the possibility of dual diagnoses may lead to additional investigations for its identification. Treatment may then be tailored to the individual's pathology.